Fisher revised scale for assessment of prognosis in patients with subarachnoid hemorrhage - Arthur Maynart Pereira Oliveira; Wellingson Silva Paiva; Eberval Gadelha de Figueiredo; Helio Araujo Oliveira; Manoel Jacobsen Teixeira (Arquivos de Neuro-Psiquiatria)
The Fisher revised scale (FRS) presents an alternative for evaluating patients with subarachnoid hemorrhage (SAH). In this study, we compared the prognosis of patients with SAH and vasospasms (VSP). METHOD: This was a prospective study on patients with a diagnosis of aneurysmal SAH, 72 hours after the initial event. Sequential neurological examinations and Hunt and Hess (HaH) score were performed on the 1st, 7th and 14th days. Transcranial Doppler was used to assess vasospasms. RESULTS: Out of the 24 patients studied, ten (41.66%) presented a delayed neurological deficit, such as diminished consciousness, decreased HaH score or death. The single patient classified as FS-1 did not have any delayed neurological deficit, while such deficits evolved in one patient out of five with FS-2 (20%); two out of seven with FS-3 (28.57%) and seven out of 11 with FS-4 (63.63%). CONCLUSION: Level three of the FS and FRS seemed to be compatible with regard to predicting the likelihood of progression to severe VSP.